Valgus Slipped Capital Femoral Epiphysis in Patient with Hypopituitarism - Yoshihiro Kotoura; Yasuhiro Fujiwara; Tatsuro Hayashida; Koji Murakami; Satoshi Makio; Yuichi Shimizu; Yoshinobu Oka; Wook-Choel Kim; Taku Ogura; Toshikazu Kubo (Case Reports in Orthopedics)
Slipped capital femoral epiphysis (SCFE) is a common disease of adolescent and the epiphysis is positioned more posteromedially in relation to the femoral neck shaft with varus SCFE; however, posterolateral displacement of the capital epiphysis, valgus SCFE, occurs less frequently. We report a case of valgus SCFE in a 17-year-old boy with hypopituitarism. After falling down, he experienced difficulty in walking. The radiographs were inconclusive; however three-dimensional computed tomography images showed lateral displacement of the epiphysis on the right femoral head. Valgus SCFE was diagnosed. The patient underwent in situ pinning of both sides. In situ pinning on the left side was performed as a prophylactic pinning because of endocrine abnormalities. At the 1-year follow-up, he could walk without any difficulty and there were no signs of pain. The epiphysis is commonly positioned more posteromedially in relation to the femoral neck shaft with most SCFE, but, in this case, the epiphysis slipped laterally. Differential diagnosis included femoral neck fracture (Delbet-Colonna type 1); however, this was less likely due to the absence of other clinical signs. Therefore, we diagnosed the patient as SCFE. When children complain of leg pain and limp, valgus SCFE that may not be visualized on anteroposterior radiographs needs to be considered.